Growth differentiation factor 5 in cartilage and osteoarthritis: A possible therapeutic candidate. (1st February 2021) - Sun, Kai; Guo, Jiachao; Yao, Xudong; Guo, Zhou; Guo, Fengjing
Abstract: Growth differentiation factor 5 (GDF‐5) is essential for cartilage development and homeostasis. The expression and function of GDF‐5 are highly associated with the pathogenesis of osteoarthritis (OA). OA, characterized by progressive degeneration of joint, particularly in cartilage, causes severe social burden. However, there is no effective approach to reverse the progression of this disease. Over the past decades, extensive studies have demonstrated the protective effects of GDF‐5 against cartilage degeneration and defects. Here, we summarize the current literature describing the role of GDF‐5 in development of cartilage and joints, and the association between the GDF‐5 gene polymorphisms and OA susceptibility. We also shed light on the protective effects of GDF‐5 against OA in terms of direct GDF‐5 supplementation and modulation of the GDF‐5‐related signalling. Finally, we discuss the current limitations in the application of GDF‐5 for the clinical treatment of OA. This review provides a comprehensive insight into the role of GDF‐5 in cartilage and emphasizes GDF‐5 as a potential therapeutic candidate in OA. Abstract : GDF‐5 is essential for cartilage development and homeostasis. GDF‐5 gene polymorphisms are significantly associated with OA susceptibility. Supplementation of GDF‐5 and regulation of its expression exhibit prominent curative effects in experimental OA and cartilage defects. GDF‐5 may be a novel potential therapeutic agent for OA.